2017
DOI: 10.1111/mmi.13881
|View full text |Cite
|
Sign up to set email alerts
|

Novel carbohydrate binding modules in the surface anchored α‐amylase of Eubacterium rectale provide a molecular rationale for the range of starches used by this organism in the human gut

Abstract: Gut bacteria recognize accessible glycan substrates within a complex environment. Carbohydrate binding modules (CBMs) of cell surface glycoside hydrolases often drive binding to the target substrate. Eubacterium rectale, an important butyrate-producing organism in the gut, consumes a limited range of substrates, including starch. Host consumption of resistant starch increases the abundance of E. rectale in the intestine, likely because it successfully captures the products of resistant starch degradation by ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…It has been suggested that the binding characteristic of a CBM improves catalytic function of the CAZymes through targeting the enzyme to the substrate and increasing substrate-enzyme proximity as well as disrupting the crystallinity of the insoluble substrate fraction (Arantes and Saddler, 2010;Reyes-Ortiz et al, 2013;Bernardes et al, 2019;Chalak et al, 2019). As a consequence, the removal of the CBM from the enzyme results in a decreased enzymatic activity (Arai et al, 2003;Cockburn et al, 2017) and a reduced enzyme stability (Bissaro et al, 2017;Courtade et al, 2018;Teo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the binding characteristic of a CBM improves catalytic function of the CAZymes through targeting the enzyme to the substrate and increasing substrate-enzyme proximity as well as disrupting the crystallinity of the insoluble substrate fraction (Arantes and Saddler, 2010;Reyes-Ortiz et al, 2013;Bernardes et al, 2019;Chalak et al, 2019). As a consequence, the removal of the CBM from the enzyme results in a decreased enzymatic activity (Arai et al, 2003;Cockburn et al, 2017) and a reduced enzyme stability (Bissaro et al, 2017;Courtade et al, 2018;Teo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the Carbohydrate Active enZymes (CAZy) database (; http://www.cazy.org/), the SBDs have been classified among the families of carbohydrate‐binding modules (CBMs). Currently, there are 83 different CBM families with 15 considered SBDs due to their ability to bind starch and related α‐glucans, such as glycogen, cyclodextrins and various maltooligosaccharides – these are CBM20, CBM21, CBM25, CBM26, CBM34, CBM41, CBM45, CBM48, CBM53, CBM58, CBM68, CBM69, CBM74, CBM82 and CBM83 . The CBM74 members are about 250 residues long and this family obviously represents a novel type of an SBD .…”
mentioning
confidence: 99%
“…Notably, similar low‐affinity CBMs in the α‐amylase that confers the capture and breakdown of starch by the related gut symbiont E. rectale have been reported. Thus, the N‐terminal CBM82 and the C‐terminal CBM83 of this α‐amylase display affinities of about 1 and 3 m m , respectively, to maltoheptaose , which is substantially lower than the internal CBMs constructs. Another example of low‐affinity ( K D = 0.58 m m for the full‐length enzyme toward β‐mannohexoase) CBM from the human gut niche is the mannan‐specific CBM10 connected to a GH5 β‐mannanase from Bifidobacterium animalis subsp.…”
Section: Discussionmentioning
confidence: 90%
“…Having large extracellular enzymes with a variety of CBMs seems to be common in Clostridiales from the human gut. R. intestinalis has a large modular GH26 mannanase with two CBMs , and both E. rectale and Butyrivibrio fibrisolvens possess large modular α‐amylases with 5 and 2 CBMs, respectively, for capturing starch . Ri CBM86 is followed by a CBM22, a GH10 catalytic module, and a tandem repeat of CBM9 (Fig.…”
Section: Discussionmentioning
confidence: 99%